KEMENANGAN DONALD TRUMP SEBAGAI PRESIDEN AMERIKA SERIKAT KE-45 MELALUI ANALISIS KONSTRUKSI KLAUSA RELATIF BAHASA INGGRIS DAN BAHASA INDONESIA SECARA SEMANTIS - Aldila Arin Aini; Islamiah Bastiar; Sumarlam Sumarlam (Universitas Muhammadiyah Surakarta, 2017)
This research aims (1) to comprehend the relative construction of English andIndonesia language on some texts relating to Donald Trump is elected as the 45thPresident of USA in 2016 semantically, and (2) to describe the analysis of relativeconstructive clauses between English and Indonesia language semantically. Theresearch method is descriptive qualitative. Meanwhile, method of collecting data isagih method and the techniques are substitution, expand, interuption, and mutation.Based on the texts relating to Donald Trump is elected as the President of USA in2016, it is found that the analysis of relative constructive clause of English andIndonesia language is based on the use of conjunction. In Indonesia language texts,there is one conjuction, namely: “yang”, meanwhile in English language texts, thereare five conjuctions, namely: “who, whom, which, whose, and that”. If it is viewedfrom its semantics adjacent, relative clause can be divided into two sections based onits orthographics, namely: (1) restrictive relative clause which refers to the explainedantecedent or as the integral unity from antecedent and unmarked by comma, and(2) non-restrictive relative clause as the additional information from antecedentexplained and marked by comma.